Different Profiles of Spatial Navigation Deficits In Alzheimer's Disease Biomarker-Positive Versus Biomarker-Negative Older Adults With Amnestic Mild Cognitive Impairment - Laczó, Martina; Martinkovic, Lukas; Lerch, Ondrej; Wiener, Jan M; Kalinova, Jana; Matuskova, Veronika; Nedelska, Zuzana; Vyhnalek, Martin; Hort, Jakub; Laczó, Jan (Frontiers in aging neuroscience, 2022)
BACKGROUND: Spatial navigation impairment is a promising cognitive marker of Alzheimer's disease (AD) that can reflect the underlying pathology. OBJECTIVES: We assessed spatial navigation performance in AD biomarker positive older adults with amnestic mild cognitive impairment (AD aMCI) vs. those AD biomarker negative (non-AD aMCI), and examined associations between navigation performance, MRI measures of brain atrophy, and cerebrospinal fluid (CSF) biomarkers. METHODS: A total of 122 participants with AD aMCI (n = 33), non-AD aMCI (n = 31), mild AD dementia (n = 28), and 30 cognitively normal older adults (CN) underwent cognitive assessment, brain MRI (n = 100 had high-quality images for volumetric analysis) and three virtual navigation tasks focused on route learning (body-centered navigation), wayfinding (world-centered navigation) and perspective taking/wayfinding. Cognitively impaired participants underwent CSF biomarker assessment [amyloid-β1-42, total tau, and phosphorylated tau181 (p-tau181)] and amyloid PET imaging (n = 47 and n = 45, respectively), with a subset having both (n = 19). RESULTS: In route learning, AD aMCI performed worse than non-AD aMCI (p < 0.001), who performed similarly to CN. In wayfinding, aMCI participants performed worse than CN (both p ≤ 0.009) and AD aMCI performed worse than non-AD aMCI in the second task session (p = 0.032). In perspective taking/wayfinding, aMCI participants performed worse than CN (both p ≤ 0.001). AD aMCI and non-AD aMCI did not differ in conventional cognitive tests. Route learning was associated with parietal thickness and amyloid-β1-42, wayfinding was associated with posterior medial temporal lobe (MTL) volume and p-tau181 and perspective taking/wayfinding was correlated with MRI measures of several brain regions and all CSF biomarkers. CONCLUSION: AD biomarker positive and negative older adults with aMCI had different profiles of spatial navigation deficits that were associated with posterior MTL and parietal atrophy and reflected AD pathology.
Keywords: allocentric navigation; entorhinal cortex; hippocampus; retrosplenial cortex; tauopathies; egocentric navigation; precuneus; neurodegeneration